FACTORS DRIVING GENERATION Z'S USE OF ONLINE FOOD DELIVERY SERVICE AT THE END OF PANDEMIC - Amelda Pramezwary; Kevin Gustian Yulius; Vinka P Viensa; Jonathan F Pujangga (Institute of Research and Community Outreach - Petra Christian University, 2023)
Food delivery industry has undergone a significant transformation with the rise of online platforms, appealing to tech-savvy Generation Z. Generation Z was chosen as they are considered the market of the future. This study examines the factors influencing Generation Z's use of online food delivery in Tangerang, during the post-COVID-19 period. Data from 150 Generation Z respondents who used online food delivery services in the past three months were analyzed using IBM SPSS version 25. The study found that perceived usefulness, trust, and time-saving benefits strongly influence Generation Z's intention to use online food delivery. They highly value the practicality, reliability, and efficiency of these platforms. Transparent communication and reliable delivery services are crucial for retaining Generation Z consumers, while highlighting the time-saving advantages is essential to meet their preferences. Surprisingly, factors like ease of use, food safety risk perception, COVID-19 severity, vulnerability, and price-saving benefits had insignificant influence. Understanding these preferences can help service providers, policymakers, and marketers enhance satisfaction and tailor their offerings to meet the needs of Generation Z in the competitive post-pandemic market. Further research is needed to uncover the specific drivers influencing Generation Z's adoption of online food delivery services.